“A casa da minha mãe era que um hospital”: Maria Pajé e seu dom de cura em São João de Pirabas - FERREIRA, Katiane de Carvalho (2023)
This article focuses on analyzing and highlighting the social and cultural mobilizations of Flaviana Serrão da Silva (1929 – 2003), popularly known as Maria Pajé, regarding her role in the work of pajelança, midwife, organization of the celebration of São Benedito, Marujada and his general collaboration regarding the local culture of São João de Pirabas. In this way, discussions regarding memory, oral history, pajelança and marujada will be presented, which will provide sustainability and scientific rigor for the development and production of the article. In this case, working with the idea of memory that consists of memories acquired from individual and collective experiences, sometimes forgotten, sometimes remembered. In relation to shamanism, it is one of the practices that Maria Pajé carried out in the city throughout her life to provide assistance, for example, with regard to health, spirituality and other benefits to everyone who sought her out. With regard to methodology, bibliographical research was carried out in accordance with the exposed theme, the use of oral history based on interviews and informal conversations carried out to compose this research. Furthermore, this study aims to make visible the memory of this woman who was essential for the city of São João de Pirabas, in addition, her record becomes relevant for the knowledge and recognition of this influential figure in this municipality.